LAST GLACIAL MAXIMUM – HOLOCENE RAINFALL SHIFTS IN THE WESTERN SAVU STRAIT BASED ON GEOCHEMICAL PROXIES - Ardi, Ryan Dwi Wahyu; Aswan, Aswan; Maryunani, Khoiril Anwar; Yulianto, Eko; Putra, Purna Sulastya; Nugroho, Septriono Hari; Nurhidayah, Efrilia Mahdilah (Engineering Faculty Universitas Lampung, 2025)
The Indo-Pacific Warm Pool significantly influences global atmospheric circulation, with tropical rainfall patterns highly sensitive to glacial–interglacial climate changes. During the Last Glacial Maximum (LGM), approximately 26,500 years before present, lower insolation, expanded ice sheets, and reduced sea levels weakened the Australian–Indonesian Monsoon (AIM) due to a southward shift of the Intertropical Convergence Zone (ITCZ). In contrast, the Holocene period experienced intensified monsoon systems and increased precipitation. However, high-resolution hydroclimate reconstructions from the western Savu Strait remain scarce. This study reconstructs rainfall variability from the LGM to the Holocene using geochemical proxies from sediment core ST10 (at 1 cm interval), located in the western Savu Strait. Three elemental ratios (Ti/Ca, K/Ca, and Rb/Sr) from X-ray fluorescence (XRF) core scanning were used to indicate terrigenous input, chemical weathering, and fluvial discharge. The age model was established using radiocarbon dating and stable isotope alignment with the Greenland ice core δ¹⁸O record. Log-transformed elemental ratios reveal four intervals of increased rainfall: the LGM, Heinrich Event 1 (HE1), Younger Dryas to Early Holocene, and the Late Holocene. These periods are characterized by elevated Ti/Ca, K/Ca, and Rb/Sr values, suggesting enhanced monsoonal rainfall and continental runoff. Conversely, lower proxy values during the Early Deglaciation, Bølling–Allerød, and Mid-Holocene indicate drier climatic conditions. These patterns align with regional proxy records from southwest Sumba and the Timor Sea, confirming the reliability of elemental ratios in reconstructing past hydroclimate variability. This study provides the first continuous record of rainfall shifts in the western Savu Strait from the LGM to Holocene and contributes to understanding long-term monsoon dynamics in southeastern Indonesia, highlighting the complex response of tropical hydroclimate to global climate forcing.